Cyclization-activated prodrugs. Synthesis, reactivity and toxicity of dipeptide esters of paracetamol - Santos, C (2005)
Dipeptide esters of paracetamol were prepared in high yields. These compounds are quantitatively hydrolyzed to paracetamol and corresponding 2,5-diketopiperazines at pH 7.4 and 37 degrees C. The reactivity is increased in sarcosine and proline peptides and decreased by bulky side chains at both the N- and C-terminal residues of the dipeptide carrier. Moreover, dipeptide esters of paracetamol did not affect the levels of hepatic glutathione. Thus, dipeptides seem promising candidates as carriers for cyclization-activated prodrugs.